Evaluation of High Amylase Corn on Growth Performance and Carcass Characteristics of Finishing Pigs - P. Ochonski; F. Wu; E. Arkfeld; J. M. Lattimer; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; J. C. Woodworth; M. D. Tokach (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 288 pigs (Line 600 × 241, DNA, Columbus, NE; initially 91.5 lb) were used in an 82-d trial to determine if replacing conventional yellow dent corn with high amylase corn (Enogen®, Syngenta Seeds, LLC) in diets with or without distillers dried grains with solubles (DDGS) influences growth performance and carcass characteristics. Pens contained 8 pigs with an equal number of barrows and gilts. There were 9 pens per treatment with pens assigned randomly to treatments balancing for initial body weight. Diets were arranged in a 2 × 2 factorial with two corn sources (conventional or high amylase) and two levels of DDGS (0 or 25%). Experimental diets were fed in meal form in 3 phases: d 0 to 29, d 29 to 47, and d 47 to 82. Pigs were weighed approximately every 2 weeks and at the start of each phase. On d 82, pigs were transported to a commercial packing plant for processing and carcass data collection. Overall, average daily gain (ADG) was marginally greater (P<0.089) for pigs fed high amylase corn than conventional corn with no evidence for difference in feed intake, feed efficiency (F/G), hot carcass weight (HCW), or other carcass traits. Added DDGS resulted in decreased (P<0.026) overall ADG and poorer (P<0.047) F/G compared to pigs fed no DDGS. Pigs fed DDGS had marginally lower (P<0.086) HCW, less (P<0.045) backfat, and marginally greater (P<0.054) loin depth, (P<0.017) percentage lean, and (P<0.0001) iodine values than pigs not consuming DDGS. The results of this trial suggest that high amylase corn tended to improve overall ADG; however, F/G and carcass characteristics were unchanged between corn sources. Further research is needed to determine if this hybrid has positive effects on growth of younger pigs or pigs fed pelleted diets.
Keywords: amylase; high amylase corn; yellow dent corn; swine